2017
DOI: 10.1002/celc.201700407
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐confined Mo2C Particles Embedded in a Porous Carbon Matrix: A Promising Anode for Ultra‐stable Na Storage

Abstract: Transition‐metal carbides (TMCs) are emerging as promising electrode materials for electrochemical energy storage devices, owing to their good conductivity and stability. Herein, Mo2C nanoparticles have been successfully encapsulated into a porous N‐doped carbon matrix through in situ confined carbonization. When evaluated as an anode material for sodium‐ion batteries (SIBs), the resultant Mo2C/N‐doped composite (Mo2C‐NC) exhibited a high rate capability and excellent cycle stability with a high capacity reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…The theoretical capacity of monolayer Mo 2 C is 132 mAh g −1 , and the average open‐circuit voltage is 0.166 eV. These results have then been experimentally confirmed 94,95 . Mo 2 C might not be appealing for high‐energy applications owing to its relatively small capacity but can be used for high‐power utilization, particularly in a hybrid system.…”
Section: Carbides Of Molybdenummentioning
confidence: 73%
See 1 more Smart Citation
“…The theoretical capacity of monolayer Mo 2 C is 132 mAh g −1 , and the average open‐circuit voltage is 0.166 eV. These results have then been experimentally confirmed 94,95 . Mo 2 C might not be appealing for high‐energy applications owing to its relatively small capacity but can be used for high‐power utilization, particularly in a hybrid system.…”
Section: Carbides Of Molybdenummentioning
confidence: 73%
“…Mo 2 C might not be appealing for high‐energy applications owing to its relatively small capacity but can be used for high‐power utilization, particularly in a hybrid system. For example, Mo 2 C/N‐C demonstrated a stable capacity of 204 mAh g −1 upon 200 cycles at 100 mA g −1 95 …”
Section: Carbides Of Molybdenummentioning
confidence: 99%
“…Again, as shown in Figure b–d, the electrochemical reaction between Mo 2 C and Li ions still brings no obvious lattice distortion and the corresponding polycrystallinity can be well maintained even after 50 and 100 long cycles, which has been clearly verified from the earlier ex situ XRD results shown in Figure . Thus, the whole specific capacity of the MCC‐T NR composite anodes may majorly come from the following: 1) the Li ions reversibly intercalate/deintercalate from the 2D layered Mo 2 C material, which is also similar to the Na‐ion storage mechanism in Mo 2 C and 2) the enlarged surface area with a micro/nanoporous structure provides more active sites for interfacial Li‐ion facile storage . Moreover, as shown in Figure S10, Supporting Information, the improved electronic conductivity of the optimized MCC‐T NR composite anodes can also be revealed from the electrochemical impedance spectroscopy (EIS) measurement.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, improvement in design of Mo 2 C nanostructure is essential to enhance their electrochemical performance. So far mostly this material has been mostly used as anode material for lithium‐ion battery with capacity around 600–900 mAh g −1 [24–30] . There are very few experimental works reported on Mo 2 C as anode material for sodium ion battery.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the TMCs, molybdenum carbides have attracted battery researchers due to its excellent metallic conductivity (∼1.02×10 2 S cm −1 ) as it provides faster electron transfer, high thermal conductivity (48.4 Wm −1 K −1 ) as it quickly dissipates the thermal energy during charging‐discharging and high capacity [19–24] . It has been observed that bulk molybdenum carbides cannot completely deliver their theoretical capacities, and on the other hand nanosized carbide materials during annealing are prone to aggregate [24–25] . Therefore, improvement in design of Mo 2 C nanostructure is essential to enhance their electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%